The magic gold fish : a Russian folktale - Demi (H. Holt, 1995)
A poor fisherman's greedy wife is never satisfied with the wishes granted her by an enchanted fish. This version adapted from Louis Zelikoff's translation of Pushkin's The tale of the fisherman and the little fish.